Economics of brucellosis impact and control in low-income countries - McDermott, John J.; Grace, Delia; Zinsstag, Jakob (2013)
Most data and evidence on the economic burden of brucellosis and the beneﬁts of its control are from high-income and middle-income countries. However, the burden of brucellosis is greatest in low-income countries. This paper focuses on estimating the economic burdens of brucellosis in low-income countries in tropical Asia and Africa. The prospects for national, technically feasible, and economically viable, national brucellosis control programmes in most low-income countries are limited. However, some targeted control programmes will be beneﬁcial and can probably be feasibly managed and provide good economic returns. More ambitious control will require a more general strengthening of Veterinary Services and livestock-sector capacity, using risk-management-based approaches.